German Cancer Consortium (DKTK) – A national consortium for translational cancer research - Stefan Joos; Dirk M. Nettelbeck; Anette Reil‐Held; Katja Engelmann; Alexandra Moosmann; Angelika Eggert; Wolfgang Hiddemann; Mechthild Krause; Christoph Peters; Martin Schuler; Klaus Schulze‐Osthoff; Hubert Serve; et al. (Molecular Oncology, 2019)
The German Cancer Consortium (‘Deutsches Konsortium für Translationale Krebsforschung’, DKTK) is a long‐term cancer consortium, bringing together the German Cancer Research Center (DKFZ), Germany's largest life science research center, and the leading University Medical Center‐based Comprehensive Cancer Centers (CCCs) at seven sites across Germany. DKTK was founded in 2012 following international peer review and has positioned itself since then as the leading network for translational cancer research in Germany. DKTK is long term funded by the German Ministry of Research and Education and the federal states of each DKTK partner site. DKTK acts at the interface between basic and clinical cancer research, one major focus being to generate suitable multisite cooperation structures and provide the basis for including higher numbers of patients and facilitate effective collaborative forward and reverse translational cancer research. The consortium addresses areas of high scientific and medical relevance and develops critical infrastructures, for example, for omics technologies, clinical and research big data exchange and analysis, imaging, and clinical grade drug manufacturing. Moreover, DKTK provides a very attractive environment for interdisciplinary and interinstitutional training and career development for clinician and medical scientists.